Beta-amyloid and cholinergic neurons - Dolezal, Vladimír; Kasparová, Jana (Neurochemical research, 2003)
It is generally accepted that the crucial events in the pathogeny of Alzheimer's disease (AD) are the increased accumulation of amyloidogenic peptides derived from amyloid precursor protein and the harmful actions of these peptides on neurons, which bring about neurodegeneration. The enhanced beta-amyloid accumulation is known to be caused by mutations of specific genes in patients who suffer from the familial (hereditary) form of AD but who represent just a minor group within the total population of AD patients. The reasons for beta-amyloid accumulation are not known in the much larger group of patients with the sporadic form of the disease. A biochemical feature common to either form of the disease is the preferential atrophy and degeneration of cholinergic neurons, which is probably responsible for much of the cognitive decline characteristic of the disease. We present an overview of recent investigations on the interactions between beta-amyloid and cholinergic neurons.
Keywords: Cholinergic Fibers; Animals; Amyloid beta-Protein Precursor; amyloidový prekurzorový protein beta; cholinergní vlákna; lidé; Neurons; amyloidní beta-protein; zvířata; fenotyp; Phenotype; Amyloid beta-Peptides; glukosa; neurony; Glucose; Humans